The pregnancy-related anxiety characteristics in women with gestational diabetes mellitus: why should we care? - Feng Fu; Ping Yan; Shuping You; Xinmin Mao; Tingting Qiao; Li Fu; Yanni Wang; Yali Dai; Palida Maimaiti (BMC, 2021)
Abstract Background Gestational diabetes mellitus (GDM) is very commonly-seen in clinical settings, and GDM patients may have higher levels of anxiety. It's necessary to evaluate the anxiety level and potentially influencing factors in patients with GDM, to provide insights for the management of anxiety of GDM patients. Methods Patients with GDM treated in our hospital from May, 2018 to May, 2020 were included. We evaluated the characteristics of patients and the scores of pregnancy-related anxiety scale for anxiety level, vulnerable personality style questionnaire (VPSQ) for personality, general self-efficacy scale (GSES) for self-efficacy, social support rating scale (SSRS) for social support level. Logistic regression analyses were conducted to identify the potential influencing factors of anxiety in GDM patients. Results A total of 386 GDM patients were included, the incidence of anxiety in patients with GDM was 59.07%. Anxiety was positively correlated with the susceptible personality (r = 0.604, p = 0.023), and it was negatively correlated with self-efficacy and social support (r = -0.586 and -0.598 respectively, all p < 0.05). The education level, monthly income, abnormal pregnancy (miscarriage, premature rupture of membranes) and cesarean section history and first pregnancy were the independent influencing factors for the anxiety in the patients with GDM (all p < 0.05). Conclusions The anxiety of GDM patients is very common, early care and interventions are warranted for those patients with abnormal pregnancy and cesarean section history, first pregnancy, lower education level, and less monthly income.